Investment Neutrality of Business Income Taxes - Hartman, Richard (Quarterly Journal of Economics, 1978)
I. Introduction, 245.—II. The model, 247.—III. The model with full investment write-off, 248.—IV. Depreciation deductions depend on the capital stock, 251.—V. Depreciation deductions depend on the time profile of past investments, 256.—VI. Concluding comments, 258.